Identification of multiple novel viruses in bar-headed goose feces from Tibet of China - Sun, Yijie; Wang, Yan; Ji, Li; Pei, Yifei; Sun, Xiaoyi; Ji, Likai; Shen, Quan; Wang, Xiaochun; Liu, Yuwei; Yang, Shixing; Zhang, Wen (Frontiers in Veterinary Science, 2024)
IntroductionThe bar-headed goose is a typical high-altitude bird that primarily inhabits alpine lakes and wetlands in Central Asia, with a remarkable ability to adapt to high elevations. Previous studies have shown that they can be infected with parasites such as Cryptosporidium spp. At present, there were few reports on its infection with the virus.MethodsIn this study, we utilized viral metagenomics to conduct a detailed analysis of the viral components in the fecal samples of bar-headed geese (Anser indicus) from the Tibet region of China.ResultsMultiple novel viruses were identified including four novel astroviruses, four novel caliciviruses, ten novel circoviruses, and nineteen novel parvoviruses. Among them, four astroviruses shared the highest amino acid sequence identities of 63.45–99.47% with different avastrovirus strains. Four caliciviruses and ten circoviruses were identified as unclassified caliciviruses and unclassified circoviruses, separately. Nineteen parvoviruses clustering into four groups maybe four different novel species of the genus Chaphamaparvovirus.ConclusionThese newly discovered viruses have potential implications for the health of avian species, particularly bar-headed geese. This study not only helps us understand the health status of bar-headed geese, but also offers crucial genomic information for future disease prevention and treatment strategies.